Ultralow-Fouling Behavior of Biorecognition Coatings Based on Carboxy-Functional Brushes of Zwitterionic Homo- and Copolymers in Blood Plasma: Functionalization Matters - Lísalová, Hana; Brynda, Eduard; Houska, Milan; Víšová, Ivana; Mrkvová, Kateřina; Song, Xue Chadtová; Gedeonová, Erika; Surman, František; Riedel, Tomáš; Pop-Georgievski, Ognen; Homola, Jiří (Analytical chemistry, 2017)
Fouling from complex biological fluids such as blood plasma to biorecognition element (BRE)-functionalized coatings hampers the use of affinity biosensor technologies in medical diagnostics. Here, we report the effects the molecular mechanisms involved in functionalization of low-fouling carboxy-functional coatings have on the BRE capacity and resistance to fouling from blood plasma. The specific mechanisms of EDC/NHS activation of carboxy groups, BRE attachment, and deactivation of residual activated groups on recently developed ultra-low-fouling carboxybetaine polymer and copolymer brushes (pCB) as well as conventional carboxy-terminated oligo(ethylene glycol)-based alkanethiolate self-assembled monolayers (OEG-SAMs) are studied using the polarization modulation infrared reflection/absorption spectroscopy, X-ray photoelectron spectroscopy, and surface plasmon resonance methods. It is shown that the fouling resistance of BRE-functionalized pCB coatings is strongly influenced by a deactivation method affecting the ultra-low-fouling molecular structure of the brush and surface charges. It is revealed that, in contrast to free carboxy-group-terminated OEG-SAMs, only a partial deactivation of EDC/NHS-activated zwitterionic carboxy groups by spontaneous hydrolysis is possible in the pCB brushes. The fouling resistance of activated/BRE-functionalized pCB is shown to be recovered only by covalent attachment of amino acid deactivation agents to residual activated carboxy groups of pCB. The developed deactivation procedure is further combined with ultra-low-fouling brushes of random copolymer carboxybetaine methacrylamide (CBMAA) and N-(2-hydroxypropyl) methacrylamide (HPMAA) with optimized CBMAA content (15%) providing a BRE-functionalized coating with superior fouling resistance over various carboxy-functional low-fouling coatings including homopolymer pCB brushes and OEG-SAMs. The biorecognition capabilities of pHPMAA-CBMAA(15%) are demonstrated via the sensitive label-free detection of a microRNA cancer biomarker (miR-16) in blood plasma.
Keywords: Polymers; molekulární struktura; Photoelectron Spectroscopy; Molecular Structure; biokompatibilní potahované materiály; Coated Materials, Biocompatible; lidé; polymery; fotoelektronová spektroskopie; Humans